Necropolitics and Imperialist Epistemicide in Western Academia in R.F. Kuang's Babel (2022) - Bilal OUADOUD; Imad Eddine TIS (UNIVERSITY OF MOHAMED BOUDIAF- M’SILA, 2025)
Abstract Western academia has historically functioned as a vehicle of imperial power, enforcing Eurocentric epistemologies while marginalizing or erasing non-Western systems of knowledge. This dissertation examines the ways in which R.F. Kuang’s Babel (2022) critiques academic institutions as instruments of imperial dominance. The main aim is to explore how the novel exposes the necropolitical and epistemic violence embedded within Western academia. It analyzes how universities legitimize imperial ideology, how language becomes a tool of domination and resistance, and how violence is framed as a morally complex but necessary response to oppression. The study draws on an interdisciplinary theoretical framework including Michel Foucault’s concepts of power/knowledge, Edward Said’s Orientalism and Contrapuntal Reading, Gayatri Spivak’s epistemic violence alongside Achille Mbembe’s necorpolitics, Frantz Fanon’s insights on colonial alienation and revolutionary violence and Boaventura de Sousa Santos’ Epistemologies of the South. Applying these theories, the analysis demonstrates that Babel is a narrative of epistemic resistance, revealing how the extraction and commodification of colonized languages enable cognitive exploitation. The findings reveal that the novel portrays academia not only as a disciplinary apparatus that produces “docile bodies,” but also as a necropolitical structure that assigns value to life based on imperial utility.